(untitled) (gjstudies, 2021)
The audit profession stands at a critical juncture, facing unprecedented challenges from technological disruption, evolving stakeholder expectations, andincreasing regulatory scrutiny. The fundamental question of how regulatoryoversight influences the long-term sustainability of this vital profession remainsinadequately addressed in contemporary literature. While numerous studieshave examined the relationship between regulation and audit quality in theshort term, few have explored the systemic implications for professional sustainability over extended horizons. This research gap is particularly concerninggiven the profession’s essential role in maintaining capital market integrity andpublic trust.Traditional approaches to audit regulation have often adopted a reductionist perspective, focusing on discrete compliance metrics without consideringthe complex adaptive nature of the audit ecosystem. The work of Ahmad etal. (2021) on coordinated approaches to fraud investigation represents an important step toward understanding integrated professional systems, yet theirframework does not extend to modeling the dynamic sustainability implicationsof regulatory interventions. Our research addresses this limitation by developinga comprehensive computational model that captures the nonlinear relationshipsbetween regulatory mechanisms and professional vitality